Baricitinib retention rate: ‘real-life’ data from a mono-centric cohort of patients affected by rheumatoid arthritis - Baldi, Caterina; Berlengiero, Virginia; Falsetti, Paolo; Cartocci, Alessandra; Conticini, Edoardo; D’Alessandro, Roberto; D’Ignazio, Emilio; Bardelli, Marco; Fabbroni, Marta; Cantarini, Luca; Frediani, Bruno; Gentileschi, Stefano (Frontiers in Medicine, 2023)
Objectives: the aim of this retrospective study was to evaluate baricitinib retention rate in patients affected by rheumatoid arthritis. Secondary aims were to compare the impact on treatment persistence of monotherapy and other variables such as systemic corticosteroid use, line of treatment, disease duration, sex, biomarkers positivity, and Herpes Zoster virus infection.Baricitinib retention rate in rheumatoid arthritis thrombosis, pulmonary embolism or tubercular infection/reactivation were reported during the study observation.Conclusions: our data show a good baricitinib retention rate after 12 and 24 months of observation (75.1% and 69.3%, respectively). In our cohort, concomitant treatment with methotrexate did not influence treatment persistence while retention was reduced in patients undergoing a steroidal treatment and/or in multi-failure subjects.